PEMBERDAYAAN AGAMA BAGI ANAK-ANAK MELALUI GERAKAN “MAGHRIB MENGAJI” DI DESA SEMANDING JENANGAN PONOROGO - Nofiya Wahyuningtyas; Siti Zazak Soraya (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
The selection of community service based on religious education, namely the reciting Al-Qur’an activity after performing the Maghrib prayer in Semanding Village, Jenangan District, Ponorogo Regency, is one of the efforts to facilitate children in learning the Al-Qur’an, which has not been available so far. The method used in implementing this community service is asset-based community development (ABCD). The community is the actor and determinant of development efforts in the environment or is often referred to as community-driven development (CDD). In addition to being a place or facility for learning the Al-Qur’an, this activity is expected to continue even after the Community Service Lecture period is over so that children have better Al-Qur’an skills. The positive impact given from the